THE PROBLEM OF MINOR WORKING CHILDREN IN HELPING TO FULFILL FAMILY NEEDS IN GAMPONG ALUE SEUTUI JEUNIEB DISTRICT BIREUEN DISTRICT - T. Aris Munandar; Rusnawati (INJOSEDU: International Journal of Social and Education, 2025)
This research is entitled "The Problem of Underage Working Children in Helping to Meet Family Needs in Gampong Alue Seutui, Jeunieb District, Bireuen Regency". The aim of this research is to find out what factors influence underage children working and what impact this has on children who work. This research uses qualitative research and uses observation, interview and documentation techniques. From the research results, researchers obtained data that the factors that cause children to have to work in Gampong Alue Seutui are based on several factors including economic factors, cultural factors, parental factors, and their own will. The family has the main view of dealing with all children who work, but the family is unable to deal with children who work because considering economic limitations, the child has to step in to meet the needs for survival. The Alue Seutui community always plays an active role in providing protection for children, however, with the very weak economic situation in the community, it is very difficult to prevent children from working. With the phenomenon of child labor like this, the government must make economic improvements for the welfare of the people, so that it is hoped that the poverty rate will decrease, which will then be followed by an increase in the quality of education in society.